Technologies For Developing Textbooks of a New Generation, Both in Printed and Electronic Form - Nigina Alimdjanovna Ashurova (Zien Journals, 2021)
This article discusses technologies for developing a new generation textbook for professionally oriented teaching of a foreign language to students of humanities universities. Having analyzed a number of textbooks and materials containing some components important in the organization of the learning process, we have identified the specific features of textbooks of the new generation, which can be positioned as requirements for them, and ways to implement them. Also, the views and opinions of many scientists on the definition of the main technologies of textbooks of the new generation in the modern world were commented on
Keywords: Textbook; technology; professionally oriented textbook; foreign language textbook